ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI ABNORMAL RETURN SAHAM PADA KINERJA JANGKA PANJANG PENAWARAN UMUM PERDANA (IPO) (Studi Kasus pada Perusahaan Non Finansial yang Go Public di Bursa Efek Indonesia Tahun 2006-2009) - Muhammad Talkhisul Abid; Harjum Muharam (JURNAL STUDI MANAJEMEN ORGANISASI, 2013)
The average stocks return of the initial public offering (IPO) in the U.S. stock market was -29.13% at the end of the third year after the IPO (Ritter, 1991). The conclusion is that the Underperformed phenomenon is influenced by the volume of trade and only occurs in the non-financial sector (Ritter, 1991). Underperformed is a stock return of initial public offerings that have lower performance compared to the market return. Bessler and Thies (2007) stated that the year of going public is the time period of the initial public offering (IPO). There is a time variation in the pattern of benefits, it raises a question of whether companies can maximize the value and amount of funds acquired. In investing, investors consider the return and risk, the expected results of the investment will be realized after a certain period of time and during this period there is a risk of the investments made. The aim of this study is to analyze the factors that affect Abnormal Return on long-term stock performance after 36 months of the IPO. The independent variables in this study consist of Benchmark, Money Raised, Market Value, and Magnitude of Underpricing. The dependent variable is the abnormal return on long-term stock performance after 36 months of the IPO. The samples used in this study were the nonfinancial companies on 2006-2009 period as many as 54 non-financial companies using purposive sampling method. The analysis technique used was multiple linear regression analysis and performed classical assumption test which include normality test, multicollinearity test, autocorrelation test, and heteroskesdasticity test. The results showed that partially the Benchmark affect significantly and negatively toward Abnormal Return; Money Raised and Market Value does not affect significantly and positively towards Abnormal Return; Magnitude of Underpricing affect significantly and positively towards Abnormal Return. The ability of the four independent variables to explain the variation on the dependent variables amounted to 45.8%, while the rest equal to 54.2% explained by other factors that are not described in the model. Keywords: Benchmark, Money Raised, Market Value, Magnitude of Underpricing and Abnormal Return